Studi Kasus Faktor-Faktor yang Memengaruhi Motivasi Belajar Siswa di SMP Negeri 1 Limpung - Iis Hidayah (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
Learning motivation is one of the key factors contributing to the success of the learning process. However, in practice, students demonstrate varying levels of learning motivation, such as low enthusiasm for classroom activities, delayed assignment completion, limited classroom participation, and difficulty maintaining concentration during lessons. These conditions highlight the importance of examining the factors influencing students' learning motivation. This study aimed to analyze the factors affecting students' learning motivation at SMP Negeri 1 Limpung. The study employed a qualitative approach using a case study design. The research subjects consisted of three students representing Grades VII, VIII, and IX, three guidance and counseling teachers, and three homeroom teachers selected through purposive sampling. Data were collected through interviews, observations, and documentation. Data validity was ensured using source triangulation and technique triangulation, while data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data collection, data condensation, data display, and conclusion drawing. The findings revealed that students' learning motivation was influenced by internal factors, including the desire to achieve success, learning needs and drives, and future aspirations, as well as external factors, including learning rewards, engaging learning activities, and a conducive learning environment. Engaging learning activities and teacher appreciation were identified as the most influential factors in enhancing students' learning motivation, whereas an unconducive learning environment and inconsistent learning drive remained obstacles for some students. The findings are expected to provide useful information for schools in designing appropriate strategies to improve students' learning motivation.